Парагангліома: випадок складного міжмагістрального розташування пухлини - Завгородній, С. М.; Перцов, В. І.; Рилов, А. І.; Воротинцев, С. І.; Доля, О. С.; Данилюк, М. Б. (Clinical Endocrinology and Endocrine Surgery, 2014)
Describes a clinical case of successful surgical treatment of patients with paraganglioma, a complex between vascular trunk location of the tumor. Include the results of laboratory and instrumental methods, described the technique of surgical intervention and methods of general anesthesia in this pathology. The paper said reaction body of the patient at the time of tumor removal and stabilization methods. Described postoperative care with correction of blood pressure after removal paragngliom.